Learning and Behavior - Mazur, James E. (Prentice Hall, 1994)
Keywords: Learning; Psychology of; Conditioned response; Behavior modification; Psychology; Comparative; dept.psy; faculty_collection

Effects of intertrial reinforcers on self-control choice. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1994)
In three experiments, pigeons chose between a small amount of food delivered after a short delay and a larger amount delivered after a longer delay. A discrete-trial adjusting-delay procedure was used to estimate indifference points-pairs of delay-amount combinations that were chosen about equally often. In Experiment 1, when additional reinforcers were available during intertrial intervals on a variable-interval schedule, preference for the smaller, more immediate reinforcer increased. Experiment 2 found that this shift in preference occurred partly because the variable-interval schedule started sooner after the smaller, more immediate reinforcer, but there was still a small shift in preference when the durations and temporal locations of the variable-interval schedules were identical for both alternatives. Experiment 3 found greater increases in preference for the smaller, more immediate reinforcer with a variable-interval 15-s schedule than with a variable-interval 90-s schedule. The results were generally consistent with a model that states that the impact of any event that follows a choice response declines according to a hyperbolic function with increasing time since the moment of choice.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-746-941-813-91X tex.type: [object Object]
Keywords: Animal; Appetitive Behavior; Choice Behavior; Color Perception; Conditioning; Operant; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Support; Non-U.S. Gov't; Support; U.S. Gov't; P.H.S.; animal; appetite; article; color vision; decision making; dept.psy; instrumental conditioning; intertrial reinforcers; key peck; motivation; pigeon; pigeons; recall; reinforcement; reinforcer amount; reinforcer delay; self‐control